Hatobangon and the Settlement of Customary Land Disputes in Sipagabu Village, Lubuk Barumun District - Hasibuan, Ningsih Erlinda (Universitas Muhammadiyah Tapanuli Selatan, 2025)
This study aims to understand the role of Customary Stakeholders (Hatobangon) in resolving customary land conflicts between the Sipagabu Village community and a forestry company, and to identify the obstacles they face in carrying out this role. The study was conducted qualitatively using a descriptive approach, collecting data through observation, in-depth interviews, and document studies. Key informants included the village head, traditional leaders, Koran teachers, residents affected by the conflict, and the village's youth. The results indicate that Hatobangon hold a strategic position as leaders of customary deliberations, guardians of customary values, and community representatives in relations with external parties. However, in the case of the transfer of customary land to the company, this role was not carried out collectively and transparently, with decisions made without full community involvement, resulting in disappointment and social conflict. The main obstacles Hatobangon faced in resolving this conflict include limited knowledge, political pressure, and a weak bargaining position in dealing with the company and the government. Nevertheless, the community still holds out hope that customary structures can be revitalized and return to their function as guardians of customary rights in a just and democratic manner.